New Rayleigh Flexible Weibull Extension (RFWE) Distribution with Applications to Real and Simulated Data. (22nd October 2022) - Javed, Muneeb; Asim, Syed Muhammad; Khalil, Alamgir; Shah, Said Farooq; Almaspoor, Zahra
Abstract : The Rayleigh flexible Weibull extension (RFWE) distribution, a new three-parameter model introduced in this paper, is a generalization of the flexible Weibull extension. This model produces best fit for failure time of electronic device obtained from power-linkage voltage spikes during electronic storms. We derive the statistical properties of the RFWE distribution. The parameters of this new distribution are estimated using the maximum likelihood method, which also yielded asymptotic confidence bounds. This model is examined using both real and simulated data. Under various priors, an additional Bayesian estimate is also carried out. The Bayes estimates and other posterior results are calculated using simulations.